Magnetic cross-linked enzyme aggregates of Km12 lipase: A stable nanobiocatalyst for biodiesel synthesis from waste cooking oil. (October 2019) - Badoei-dalfard, Arastoo; Malekabadi, Saeid; Karami, Zahra; Sargazi, Ghasem
Abstract: Enzymatic production of biodiesel from waste cooking oils (WCOs) is expected as an efficient procedure for resolving the problems of energy demand and environment pollutions. But, high cost of lipases has been found as a main obstacle to commercialize the enzymatic transesterification. In the present study, cross-linked enzyme aggregates of Km12 lipases have been coupled with amino coated magnetite nanoparticles. SEM analysis showed that mCLEAs-lipase (mCLEAs-lip) nanocomposites have spherical structures. The mCLEAs-lip displayed a shift in optimal pH towards the alkaline, whereas optimal temperature was also shift towards low temperature. mCLEAs-lip nanocomposite reserves its total activity up to 6 cycles of enzyme re-using. Furthermore, it reserves 60% of its initial activity more than free enzyme after 24 days of incubation at 4 °C. Biodiesel production from waste cooking oils by immobilized enzyme increased about 20% more than free enzyme. Therefore, the present study displays great practical latent to produce renewable fuel such as biodiesel. Graphical abstract: Image 10844 Highlights: mCLEAs-lip displayed a shift in optimal pH towards the alkaline. mCLEAs-lip displayed a shift in optimal temperature towards low temperature. mCLEAs-lip reserved 60% of storage activity compare to free enzyme. mCLEAs-lip produced biodiesel 25% from WCO more than free enzyme. mCLEAs-lip reserved its total activity up to 6 cycles.